The role of elites in economic development : a study prepared for the World Institute for Development Economics Research of the United Nations University (UNU-WIDER) - Amsden, Alice H. (Alice Hoffenberg); DiCaprio, Alisa; Robinson, James A., 1960-; World Institute for Development Economics Research (Oxford : Oxford University Press, 2012)
Elites play a crucial role in the development process. The impact they have on growth and development exceeds their representation within a country. This volume uses case studies from South Africa to China to seek an understanding of the relationship between elites and economic development.
Series from dust jacket.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Development economics; Development economics -- Social aspects; Elite (Social sciences) -- Economic conditions